Reflections on the problem of social cohesion and the argentine historiographic field around the centennial (Estudios Sociales, 2019)
The reformist commitment to assume the economic inequality and channel the social conflict in Argentina, during the end of the XIX Century and the first decade of the XX Century, sparked the deployment and articulation of several cohesive policies, among of which was the creation of identity bounds able to generate solidarities beyond both the socioeconomic fracture and the ethnic heterogeneity. The state intervened innovatively on the historical knowledge in order to institutionalize it, to be able to produce a documented-contrasted-objective knowledge about the Argentinian past. Its ultimate aim was to build nationality. This state intervention triggered both the constitution of the Argentinean Historiography understood as a discipline and the relative autonomy of the Historiographic field.